The Use of E Voting in the General Election System in Indonesia - Muhammad Budiana (LEGAL BRIEF, 2022)
As a nation that conforms to the concept of democracy, Indonesia is expected to hold honest and fair elections that comply to the ideals of being direct, general, free, and confidential. In order for the results of general and regional head elections to insire confidence in all parties, openness and accountability must be referenced during these contests. Building a network architecture that enables transparent implementation of the election itself is one of the most challenging aspects of establishing a democratic party. This study intends to examine the future use of electronic voting in Indonesia's electoral system. This study employs a qualitative, descriptive methodology. In an effort to increase voter participation, reduce the impact of fraud in vote counting, reduce costs, and shorten implementation time, the results indicate that electronic voting can be used as an alternative method for general elections due to the Constitutional Court's decision number 147/PUU-VII/2009. Considering the circumstances of the 2019 election in which there were numerous casualties. In addition to having a positive impact, the implementation of e-voting also cannot be separated from problems such as short preparation time, budget problems, readiness of facilities and infrastructure such as uneven internet availability and finally the readiness of resources.